Appendix 3.3: Excerpts from “Project Appraisal Document on the Purchase of Emission Reductions Proposed by the Prototype Carbon Fund in the Amount of USD 1.5 Million to the Northwind Power Development Corporation for a Northwind Bangui Bay Project” - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
This document shows that the Bangui windmills are a private venture, specifically of the Northwind Power Development Corporation (NWPDC). Of local government involvement in the project, the document states that NWPDC “enjoys the support of the provincial government of Ilocos Norte.” Nothing in the document indicates that the project was initiated by then governor Bongbong Marcos.